Clinical and molecular study of patients with thyroid dyshormogenesis and variants in the thyroglobulin gene - Fernández-Cancio, Mónica; Antolín, María; Clemente, María; Campos-Martorell, Ariadna; Mogas, Eduard; Baz-Redón, Noelia; Leno-Colorado, Jordi; Comas-Armangué, Gemma; García-Arumí, Elena; Soler-Colomer, Laura; González-Llorens, Núria; Camats-Tarruella, Núria; et al. (Frontiers in Endocrinology, 2024)
Introduction: Defects in any thyroid hormone synthesis steps cause thyroid dyshormonogenesis (THD). THD due to thyroglobulin (TG) gene variants is a cause of congenital hypothyroidism (CH) with a wide clinical spectrum, ranging from mild to severe permanent hypothyroidism. We present high-throughput sequencing results of patients with TG variants.Method: A CH high-throughput sequencing-panel of the main genes involved in the regulation of thyroid hormonogenesis was performed to identify those TG variants that may be related to patient THD phenotype.We identified 21 TG gene variants in 19 patients (11.8%) which could explain their phenotype. Ten of those (47.6%) were not previously described. CH was biochemically severe in these 19 patients. Eight of them were reevaluated after one month of discontinuing LT4 treatment and all had severe permanent hypothyroidism. We also identified another 16 patients who presented heterozygous TG variants, of whom, at reevaluation, five had mild permanent and only one had severe permanent hypothyroidisms.Eliminado: A total of 160 patients from the CH Neonatal Discussion: In this study, 10 novel and 11 previously reported variants in the TG gene have been identified that could explain the phenotype of 19 patients from non-consanguineous families from a large THD cohort. Although not all these TG gene variants can explain all the patients' THD phenotypes, some of them had severe or mild permanent hypothyroidism at reevaluation.